Proteinuria assessment in preeclampsia: a comparative study - Sneha, Shriti; Mittal, Rita; Rigveda, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Preeclampsia, a severe pregnancy-related hypertensive disorder, presents substantial maternal and fetal health risks. Accurate proteinuria assessment is crucial but traditional methods are cumbersome and error-prone. This study compares the spot urinary protein/creatinine ratio with 24-hour urine collection for proteinuria estimation in preeclampsia at Kamla Nehru State Hospital for Mother and Child. Methods: A cross-sectional study with 90 eligible pregnant women collected comprehensive medical data. Both spot urinary protein/creatinine ratios and 24-hour urine collections were analyzed. Strong correlation (r=0.942, p<0.0001) was observed. Results: Spot urinary protein/creatinine ratio demonstrated moderate diagnostic accuracy (AUC=0.3). Sensitivity was 100%, specificity 87.9%, with PPV and NPV at 90.4% and 92%, confirming its clinical utility for proteinuria diagnosis. Conclusions: This study validates the spot urinary protein/creatinine ratio as an efficient method for proteinuria assessment in preeclampsia, with a strong correlation and high diagnostic value. Widespread adoption has the potential to expedite diagnosis, enhance outpatient care, and improve outcomes for preeclampsia patients, addressing a crucial healthcare challenge in maternal and fetal health.